Liquid Crystalline Nanostructures as PEGylated Reservoirs of Omega-3 Polyunsaturated Fatty Acids: Structural Insights toward Delivery Formulations against Neurodegenerative Disorders - Angelova, Angelina; Drechsler, Markus; Garamus, Vasil M; Angelov, Borislav (ACS omega, 2018)
Omega-3 polyunsaturated fatty acids (ω-3 PUFAs) are bioactive lipids with considerable impact in medicine and nutrition. These compounds exert structuring effects on the cellular membrane organization, regulate the gene expression, and modulate various signaling cascades and metabolic processes. The purpose of the present work is to demonstrate the structural features of ω-3 PUFA-containing three-dimensional supramolecular lipid assemblies suitable for pharmaceutical applications that require soft porous carriers. We investigate the liquid crystalline structures formed upon mixing of eicosapentaenoic acid (EPA, 20:5) with the lyotropic nonlamellar lipid monoolein and the formation of multicompartment assemblies. Starting with the monoolein-based lipid cubic phase, double membrane vesicles, cubosome precursors, sponge-type particles (spongosomes), mixed intermediate nonlamellar structures, and multicompartment assemblies are obtained through self-assembly at different amphiphilic compositions. The dispersions containing spongosomes as well as nanocarriers with oil and vesicular compartments are stabilized by PEGylation of the lipid/water interfaces using a phospholipid with a poly(ethylene glycol) chain. The microstructures of the bulk mixtures were examined by cross-polarized light optical microscopy. The dispersed liquid crystalline structures and intermediate states were studied by small-angle X-ray scattering, cryogenic transmission electron microscopy, and quasielastic light scattering techniques. They established that PUFA influences the phase type and the sizes of the aqueous compartments of the liquid crystalline carriers. The resulting multicompartment systems and stealth nanosponges may serve as mesoporous reservoirs for coencapsulation of ω-3 PUFA (e.g., EPA) with water-insoluble drugs and hydrophilic macromolecules toward development of combination treatment strategies of neurodegenerative and other diseases.